Nuclear Structure Studies in the 132Sn Region: "Safe Coulex" with Carbon Targets. (August 2015) - Allmond, J M; Stuchbery, A E; Galindo-Uribarri, A; Padilla-Rodal, E; Radford, D C; Batchelder, J C; Bingham, C R; Howard, M E; Liang, J F; Manning, B; Pain, S D; Stone, N J; et al.
Abstract: The collective and single-particle structure of nuclei in the 132 Sn region was recently studied by Coulomb excitation and heavy-ion induced transfer reactions using carbon, beryllium, and titanium targets. In particular, Coulomb excitation was used determine a complete set of electromagnetic moments for the first 2 + states and one-neutron transfer was used to probe the purity and evolution of single-neutron states. These recent experiments were conducted at the Holifield Radioactive Ion Beam Facility at ORNL using a Csl-HPGe detector array (BareBall- CLARION) to detect scattered particles and emitted gamma rays from the in-beam reactions. A Bragg-curve detector was used to measure the energy loss of the various beams through the targets and to measure the radioactive beam compositions. A sample of the Coulomb excitation results is presented here with an emphasis placed on 116 Sn. In particular, the "safe Coulex" criterion for carbon targets will be analyzed and discussed.